Pendampingan Tata Kelola Desa Wisata dengan Pelatihan Pelayanan Prima dan Bahasa Inggris untuk Pariwisata di Desa Bedono Demak - Nur Fitriyani; Mella Narolita; Hamsar Suci Amalia; Aulia Restu Ariyanto Putri; Sarah Iasya (Lembaga Pengembangan Kinerja Dosen, 2025)
A community service program in Bedono Tourism Village, Demak, focuses on enhancing service quality and English language proficiency for tourism purposes through integrated training. Partnering with the Demak Tourism Awareness Group (Pokdarwis), the program targets youth organization members, tour guides, and local tourism activists. The initiative addresses challenges such as limited learning resources, lack of government support, low motivation to learn, and insufficient awareness of English usage in tourism communication. To tackle these issues, the program offers training on service excellence and English language, aiming to improve participants' communication skills for tourism needs. The activities encompass educating on service concepts, creating integrated training materials, introducing basic English for tourism, conducting role-play simulations, and evaluating foreign tourist service practices, ultimately aiming to enhance the community's tourism service standards.